The relationship between vegetable price fluctuation and food expenditure share in Indonesia during and after the COVID-19 pandemic (2020–2024) - Ayuning Mawar Pringgani (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The COVID-19 pandemic disrupted food systems globally, triggering price volatility and changes in household consumption patterns, especially in developing economies such as Indonesia. This study examines the relationship between vegetable price fluctuation and food expenditure share per capita in Indonesia during and after the COVID-19 pandemic (2020–2024). Methods: Five major vegetable commodities (shallots Allium cepa var. aggregatum, curly red chili Capsicum annuum, large red chili Capsicum annuum, bird’s eye chili Capsicum frutescens, and garlic Allium sativum) were analyzed using secondary data from the Indonesian Central Bureau of Statistics (BPS). The analysis combined descriptive statistics with Pearson correlation and simple linear regression using SPSS. Findings: Results revealed a strong negative correlation (r = –0.935) between average vegetable price fluctuation and food expenditure share per capita, indicating that greater price stability was associated with higher food spending among households. This suggests that the normalization of vegetable markets and improved price stability in the post-pandemic period encouraged households to allocate a larger portion of their income to food consumption. Higher food expenditure shares are likely to support increased vegetable consumption, improved diet diversity, and better nutritional adequacy, particularly for micronutrient-rich foods. The regression model further showed that 87.4% of the variation in food expenditure share could be explained by changes in vegetable price fluctuation (R² = 0.874). Conclusion: These findings highlight the importance of maintaining price stability for perishable commodities as part of Indonesia’s post-pandemic food security recovery strategy through improved supply chains, logistics, and market integration. Stable vegetable prices may play a critical role not only in stabilizing household food spending but also in promoting healthier and more diverse diets. Novelty/Originality of this article: This study provides one of the first empirical assessments of how vegetable price fluctuations during and after the COVID-19 pandemic influenced household food expenditure behavior in Indonesia.